Studi Maksimal Cekam pada Ragum Hidrolik - Indra Harwanto P; Pranowo Sidi; Budianto Budianto (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Indonesia has a lot of livelihoods, especially in industry. Because the Indonesian people are very numerous, the production each year will increase, therefore every producer must be able to overcome every need that consumers want. The manufacturing field is most needed in every industry because every product manufacture must not be separated from the manufacturing process. In a worksheet there must be a hand work tool to facilitate or tidy up a final process. In this case the viscera function as a tool for clamping workpieces is very important. Ragum is a clamping device to clamp the workpiece that will be carried out by the milling process. With the vise, the workpiece can be tightly clamped so as to facilitate the processing process and the results of a process will be maximized. In this Final Project, a maximum stress strength analysis will be carried out on one of the Hydraulic Rigs with the aim that the Raft can be more efficient and operate optimally. The study conducted on this hydraulic formula is expected to be able to overcome problems that often occur in the manufacturing process in the field of production. So that the operator knows more about the work of the hydraulic vise and can operate optimally, and the production work is not hampered due to damage to the vise. In the end, the hydraulic vise will be able to be used longer than the vise that is used carelessly and quickly damaged.